2021
DOI: 10.48550/arxiv.2111.00630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long time decay and asymptotics for the complex mKdV equation

Abstract: We study the asymptotics of the complex modified Korteweg-de Vries equation ∂tu + ∂ 3x u = ±|u| 2 ∂xu In the real valued case, it is known that solutions with small, localized initial data exhibit modified scattering for |x| ≥ t 1/3 , and behave self-similarly for |x| ≤ t 1/3 . We prove that the same asymptotics hold for complex mKdV. The major difficulty in the complex case is that the nonlinearity cannot be expressed as a derivative, which prevents us from using the scaling vector field to get control in wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…See e.g. [48,10]. We expect a similar behavior of the weakly localized part of the solutions of KG equations.…”
Section: Introductionmentioning
confidence: 60%
“…See e.g. [48,10]. We expect a similar behavior of the weakly localized part of the solutions of KG equations.…”
Section: Introductionmentioning
confidence: 60%
“…However, by writing the inner product in the Fourier domain and using trigonometric identities it is possible, in essence, to move the portion of the cos multiplier that is responsible for the bilinear decay from nw n onto the |u n | 2 term (see Corollary 7), recovering the t −1 decay and letting us control this term. Although this identity might appear miraculous, it should also be expected, since a similar identity holds for complex mKdV using integration by parts (see [28]).…”
Section: 34mentioning
confidence: 81%
“…Proof. We will focus on proving (28): the argument for (29) is similar. Using the support assumptions on f n and h n and (26), we can write…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [29] it is shown that for small data there is a spreading weakly localized part for the KdV type equation.…”
Section: Introductionmentioning
confidence: 99%